A Dynamic Stochastic Model of Medical Care Use and Work Absence - Gilleskie, Donna B. (Econometrica, 1998)
This research explores the medical care consumption and absenteeism decisions of employed individuals with acute illnesses in an effort to better understand health care behavior. Using data from the 1987 National Medical Expenditure Survey, the author estimates the structural parameters of an individual's discrete choice stochastic optimization problem, as opposed to employing conventional reduced form estimation methods that are prevalent in the health care literature. The estimates allow for predictions of the change in physician services use and illness-related absenteeism that arise with the introduction of new public policy initiatives involving health insurance and sick-leave coverage.